LENGTH-WEIGHT RELATIONSHIPS OF 12 FISH IN A TROPICAL ESTUARY FROM NORTHEAST BRAZIL: Relações comprimento-peso de 12 peixes em um estuário tropical do Nordeste do Brasil - Lima, Severino Adriano Oliveira; Agrelli Andrade, Humber (Arquivos de Ciências do Mar, 2021)
Estuarine environments are highly dynamic supporting a great fish species diversity. The present study was conducted to estimate length-weight relationships for 12 fish species from the Canal de Santa Cruz system using conventional methods and Bayesian analysis. The samples were collected in one day each month between July 2013 and June 2014, obtained using gillnets (100 to 200 × 2.2 m, mesh size 30, 40, and 50 mm). A total of 12 fish species representing 3 orders and 6 families were analyzed. Of the 12 species in the present study, only Diapterus auratus, Diapterus rhombeus and Bairdiella ronchus were analyzed in Pernambuco state, and there is a limited of analysis for the species Strongylura marina, Harengula clupeola, Opisthonema oglinum, Anchovia clupeoides, Anchoa tricolor and Oligoplites saurus in region Northeast Brazil. Keywords: icthyofauna, allometry, condition factor, bayesian analysis.